Effects of intraoperative diltiazem infusion on flow changes in arterial and venous grafts in coronary artery bypass graft surgery - Erdem,Ozan (2015)
Abstract Objective: This study aimed to show the effects of intra-operative diltiazem infusion on flow in arterial and venous grafts in coronary artery bypass graft surgery. Methods: Hundred fourty patients with a total of 361 grafts [205 (57%) arterial and 156 (43%) venous] underwent isolated coronary surgery. All the grafts were measured by intraoperative transit time flow meter intra-operatively. Group A (n=70) consisted of patients who received diltiazem infusion (dose of 2.5 microgram/kg/min), and Group B (n=70) didn't receive diltiazem infusion. Results: Mean graft flow values of left internal mammary artery were 53 ml/min in Group A and 40 ml/min in Group B (P<0.001). Pulsatility index (PI) values of left internal mammary artery for Group A and Group B were 2.6 and 3.0 respectively (P<0.001). No statistically significant difference was found between venous graft parameters. Conclusion: We recommend an effect of diltiazem infusion in increasing graft flows in coronary artery bypass graft operations.